Sisaret - Ria Karhila; Olli Haikka; Riina Hyytiä; Sirpa Hyttinen; Eppu Nuotio; Petri Pystynen; Antti Haikala; Petri Pystynen; Antti Haikala; Mika Toivanen; Jari Sillanpää; Eppu Nuotio (2003)
Kahden keski-ikäisen sisaren elämää muutoksien aallokossa.